Mirounga leonina - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Mirounga leonina (Linnaeus 1758) [Phoca] leonina Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 37. Type Locality: "ad polum Antarcticum" restricted by Thomas (1911 a ) to "Juan Fernandez", further restricted by Hamilton (1940) as " Isla Mas a Tierra" [Chile]. Vernacular Names: Southern Elephant Seal. Synonyms: Mirounga crosetensis (Lydekker 1909); Mirounga falclandica (Peters 1875); Mirounga kerguilensis (Peters 1875); Mirounga macquariensis (Lydekker 1909); Mirounga typicus (Lydekker 1909). Distribution: Circumpolar mainly in the subantarctic zone, including Antarctica, Macquarie, Kerguelen, S Georgia Isls, and Argentina (Peninsula Valdez). Vagrant populations recorded at Australia, Brazil, Chile, Mauritius, Mozambique, Namibia, New Zealand, Oman, Uruguay. Conservation: CITES – Appendix II; IUCN – Lower Risk (lc). Discussion: Reviewed by Ling and Bryden (1992). Synonyms allocated according to Bryden (1995). Subspecies not recognized, following Lönnberg (1910); however see Carrick et al. (1962). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 597, DOI: 10.5281/zenodo.7316519